Genetic diversity of potato varieties bred in Russia and near-abroad countries based on polymorphism of SSR-loci and markers associated with resistance R-genes - O. Y. Antonova; N. A. Shvachko; L. Y. Novikova; O. Y. Shuvalov; L. I. Kostina; N. S. Klimenko; A. R. Shuvalova; T. A. Gavrilenko (Вавиловский журнал генетики и селекции, 2016)
The genetic diversity of potato varieties from the VIR collection was analyzed based on microsatellite analysis. These varieties have been bred in Russia and near-abroad countries since the 1931. Application of 14 highly polymorphic nuclear microsatellites (SSR) enabled the complete discrimination of all 113 varieties. Additionally, we have studied these varieties for the distribution of 8 DNA markers associated with three R-genes involved in the control of resistance to two quarantine objects: the potato wart Synchytrium endobioticum and golden potato cyst nematode Globodera rostochiensis, which occur locally in some regions of the Russian Federation. All the analyzed varieties with resistance to S. endobioticum pathotype 1 revealed the diagnostic marker Nl-251400 of the Sen1 gene and a few susceptible cultivars lost this diagnostic fragment. The tested markers of the H1 and Gro1-4 genes, which confer resistance to G. rostochiensis pathotype Ro1 revealed different predictiveness. In the molecular screening of potato varieties, it is better to use several markers of these genes. Results of molecular screening using six markers of the H1 and Gro1-4 genes allowed us to detect 6 haplotypes in the tested subset. Five haplotypes include varieties with different combinations of the markers tested, the majority (87.9 %) of these varieties were highly resistant or moderately resistant to G. rostochiensis. The most numerous haplotype H1/0 included 76 varieties, which did not possess any marker; 96.1 % of these varieties were susceptible to G. rostochiensis. Predictive associations between haplotype content, wart and nematode resistance, pedigree and ‘variety age’ are discussed.